Topoisomerase II-Induced Chromosome Breakage and Translocation Is Determined by Chromosome Architecture and Transcriptional Activity - Canela, Andres (Mol Cell, 2019)
Topoisomerase II (TOP2) relieves torsional stress by forming transient cleavage complex intermediates (TOP2ccs) that contain TOP2-linked DNA breaks (DSBs). While TOP2ccs are normally reversible, they can be “trapped” by chemotherapeutic drugs such as etoposide and subsequently converted into irreversible TOP2-linked DSBs. Here, we have quantified etoposide-induced trapping of TOP2ccs, their conversion into irreversible TOP2-linked DSBs, and their processing during DNA repair genome-wide, as a function of time. We find that while TOP2 chromatin localization and trapping is independent of transcription, it requires pre-existing binding of cohesin to DNA. In contrast, the conversion of trapped TOP2ccs to irreversible DSBs during DNA repair is accelerated 2-fold at transcribed loci relative to non-transcribed loci. This conversion is dependent on proteasomal degradation and TDP2 phosphodiesterase activity. Quantitative modeling shows that only two features of pre-existing chromatin structure—namely, cohesin binding and transcriptional activity—can be used to predict the kinetics of TOP2-induced DSBs.